First International Conference on Availability, Reliability and Security (ARES'06) 2006
DOI: 10.1109/ares.2006.133
|View full text |Cite
|
Sign up to set email alerts
|

The usability and practicality of biometric authentication in the workplace

Abstract: This paper discusses usability and practicality issues for authentication systems based on biometrics.The effectiveness of a system incorporating an authentication method depends not only on theoretical and technological issues, but also on user interaction with and practical implementation of the system by an organisation. It is becoming increasingly common that IT and physical security are converging, especially in the workplace. This has significant ramifications for the workforce and operational matters. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Notably, reasearchers have found the acceptance of a fingerprint authentication system to change based on context (personal versus purchasing) [22]. Subtle issues in deployment, like the height of face scanners and the hygiene of fingerprint scanners, also have a major impact on perception and therefore adoption [23].…”
Section: Related Workmentioning
confidence: 99%
“…Notably, reasearchers have found the acceptance of a fingerprint authentication system to change based on context (personal versus purchasing) [22]. Subtle issues in deployment, like the height of face scanners and the hygiene of fingerprint scanners, also have a major impact on perception and therefore adoption [23].…”
Section: Related Workmentioning
confidence: 99%
“…Another work on biometric authentication for an Android device [23] showed an increased level of higher task efficiency achieved using various solution. In [24], authors studied the usability and practicality of biometric authentication in the workplace and concluded that the ease of technology utilization and its environmental context play a vital role while the integration and the adoption will always incur additional and unexpected resource costs.…”
Section: Ismentioning
confidence: 99%
“…There are now several large-scale, public facing implementations of biometric systems, including the US-VISIT scheme and the proposed identity card scheme in the United Kingdom. Secondly, the increase of computer security incidents and the need to safeguard information will contribute to an increased usage of biometric technology [4,5]. Finally, biometric technology is often described as a positive development for the public at large [6].…”
Section: Introductionmentioning
confidence: 99%